High performance liquid chromatographic determination of free cisplatin in different cancer types - (:unkn) unknown (My University, 2013)
Cisplatin (CDDP) is an old antineoplastic agent used for cancer treatment alone or combined with other agents. Nonprotein-bound (free) cisplatin levels is directly related to the cisplatin-induced nephrotoxicity. Therefore, therapeutic drug monitoring is very important for cisplatin. Findings of this study will help for determination of free cisplatin which can be appropriate for therapeutic drug monitoring. Cisplatin was analyzed by HPLC using a C18 endcapped column and mobile phase consisted of methanol and water (80:20, v/v), the UV detector was adjusted at 254 nm. The mobile phase was maintained at 1mL min-1 and the column temperature was ambient temperature. The method was validated for specificity, linearity, precision and accuracy. Linearity of the method was found to be in the concentration range of 0.025-2.00 μg/ml. The limit of detection (LOD) and the limit of quantification (LOQ) were 0.008 μg/ml and 0.025 μg/ml. To evaluate the practical applicability of our method, a total of 35 cancer patients' blood were analyzed. The significant differences were found between the concentration of free cisplatin and different cancer types.
Keywords: Cisplatin determination; Clinical pharmacy; Hplc; Human plasma; Therapeutic drug monitoring